Factors Affecting Adherence to Pediatrics Antiretroviral Therapy in Mekelle Hospital, Tigray Ethiopia - Teklemariam Gultie; Tesfay G/Amlak; Girum Sebsibie (Intelektual Pustaka Media Utama, 2015)
The most important factor in the success of HIV treatment is adherence to antiretroviral therapy (ART).The challenge to adherence to ART is particularly serious in Sub-Saharan Africa as the high rates of HIV/AIDS lead to greater numbers of affected individuals. Although long-term good ART adherence has been observed in certain settings of public sectors the magnitude of this challenge in Sub-Saharan Africa remains large and there is evidence for high rates of patient’s poor adherence. Study aimed to assess the factors affecting adherence to pediatrics antiretroviral therapy (ART) among children in Mekelle hospital, Tigray, Ethiopia. A Hospital based cross-sectional study was conducted on 226 children on antiretroviral therapy from May 01 to 30/2014 at Mekelle hospital. Data was collected from care givers of children under 15 years old who are on ART. Of the 226 children under 15 years, 90.3 % reported complete adherence to antiretroviral therapy medications at the regular schedule over the past 7 days. Factors associated with adherence were having male care giver (AOR=2.10[1.01, 7.22]), age of the child (AOR=1.43[1.16, 3.98]) below 5 years and use of first line ART drugs (AOR=2.86[1.54, 3.67]). Over all the adherence of children on ART to their medication in this study is relatively higher as compared to others. However, complete adherence is expected in order to make the drugs effective. Different strategies have to be designed to improve the adherence level.